Study of radiation dose distribution for 6MV photon beam product from VARIAN IX linac in case of large fields using BEAMnrc and DOSXYZnrc codes - جبيلي هيثم; بدوي محمد عبد الحكيم; المحمود أيهم; محرز ميلاد (Latakia University Journal -Basic Sciences Series, 2022)
Monte Carlo model of 6MV photon beam output profile of Varian ix linear accelerator was validated by comparing computed Percentage Depth Dose and Dose Profile curves with measured TPS curves. Monte Carlo calculation method is the most accurate for calculating dose in radiotherapy. In this paper, BEAMnrc code was used to model the head of linear accelerator and simulate photon beam, and DOSXYZnrc code to calculate absorbed dose within phantom. percentage depth dose (PDD) and dose profile distribution curves (6 MV) were calculated for large fields 25 × 25 cm2, 30 × 30 cm2 and 35 × 35 cm2. BEAMnrc and DOSXYZnrc were used to perform all dose calculations in this paper. PDD calculated using Monte Carlo was compared with values ​​calculated using Treatment Planning System (TPS). Good agreement was found between PDD computed using Monte Carlo simulation and the TPS calculation with a maximum dose difference of 4.3% for PDD and 3.55% for the dose profile curves. The results showed that the different components of simulated linear accelerator were precisely modeled using Carlo death simulation. In conclusion, BEAMnrc and DOSXYZnrc codes package has very good accuracy in calculating dose distribution of 6 MV photon package and can be considered as a promising method for calculating patient dose.